2013
DOI: 10.1039/c3dt51120k
|View full text |Cite
|
Sign up to set email alerts
|

Quick and selective synthesis of Li6[α-P2W18O62]·28H2O soluble in various organic solvents

Abstract: Herein we report the synthesis of α-Dawson type POM, Li6[α-P2W18O62]·28H2O, directly from the use of Li2WO4 as the tungstate source. The salt obtained was soluble not only in water but also in a range of polar and non-polar organic solvents, such as benzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…In the course of our research on the Preyssler anion, we have reported that the ammonium salt of the Keggin anion (NH 4 ) 3 [PW 12 O 40 ] was formed when ammonium metatungstate (NH 4 ) 6 [H 2 W 12 O 40 ] was used as the tungsten source, in spite of a large P/W ratio of 3.0 6. Recently, Nishihara's group reported that the lithium salt of the Dawson anion Li 6 [P 2 W 18 O 62 ] was formed when lithium tungstate (Li 2 WO 4 ) was used as the tungsten source, in spite of a P/W ratio of 4.8 7. These results inspired us to investigate the cation effect in the synthesis of the 30‐tungsto‐5‐phosphate systematically.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the course of our research on the Preyssler anion, we have reported that the ammonium salt of the Keggin anion (NH 4 ) 3 [PW 12 O 40 ] was formed when ammonium metatungstate (NH 4 ) 6 [H 2 W 12 O 40 ] was used as the tungsten source, in spite of a large P/W ratio of 3.0 6. Recently, Nishihara's group reported that the lithium salt of the Dawson anion Li 6 [P 2 W 18 O 62 ] was formed when lithium tungstate (Li 2 WO 4 ) was used as the tungsten source, in spite of a P/W ratio of 4.8 7. These results inspired us to investigate the cation effect in the synthesis of the 30‐tungsto‐5‐phosphate systematically.…”
Section: Introductionsupporting
confidence: 81%
“…–12.54 ppm corresponding to the two equivalent P atoms in the alpha isomer of the Dawson anion was observed, and two small singlets with 1:1 integration ratio at –11.06 and –11.80 ppm corresponding to the two P atoms in the beta isomer of the Dawson anion were observed 7. This result is similar to Nishihara 's result where Li 2 WO 4 was used as tungsten source 7. We also confirmed that the Dawson anion is detected as the only product when Li 2 WO 4 was used as W‐source under our conditions (Figure 4a, no.…”
Section: Resultsmentioning
confidence: 99%
“…[28] This allowso ne to scrutinize the influence of the size effecto ft he PMs on the self-assembly of peptides. We herein chose several PM clusters (PM-n, n = 1-7, Figure1a), such as Na 6 [V 10 O 28 ]( PM-1), [29] Na 9 [PW 9 O 34 ]( PM-2), [30] H 4 [SiW 12 O 40 ]( PM-3), K 6 [P 2 W 18 O 62 ]( PM-4), [31] K 12.5 Na 1.5 [NaP 5 W 30 O 110 ]( PM-5), [32] [33] and (NH 4 ) 42 [Mo 132 O 372 (CH 3 COO) 30 (H 2 O) 72 ]( PM-7). [34] The estimated sizes of these PMs are summarizedi nT able 1 based on their crystal structures (CIF data).…”
Section: Resultsmentioning
confidence: 99%
“…Materials H 4 [SiW 12 O 40 ]( PM-3) was acquired from Aladdin GmbH, Na 6 [V 10 O 28 ] (PM-1), [29] Na 9 [PW 9 O 34 ]( PM-2), [30] K 6 [P 2 W 18 O 62 ]( PM-4), [31] K 12.5 Na 1.5 [NaP 5 W 30 O 110 ]( PM-5), [32] K 28 L i5 [H 7 (P 8 W 48 O 184 )]·92 H 2 O( PM-6), [33] and (NH 4 ) 42 [Mo 132 O 372 (CH 3 COO) 30 (H 2 O) 72 ]( PM-7) [34] were prepared according to reported procedures. Fmoc-Rink amide MBHA (4-methylbenzhydrylamine hydrochloride) resin (0.65 mmol g À1 ) was obtained from Advanced Chem Te ch.…”
Section: Methodsmentioning
confidence: 99%
“…Darker and lighter polyhedra in (B) represent the cap and belt types of tungsten sites, respectively. The Wells-Dawson structure by Kato et al (2013) with refcode RIBFUF is the structure with the lowest R 1 value reported (Kato et al, 2013) and is used in this work as a reference Wells-Dawson structure.…”
Section: Introductionmentioning
confidence: 99%